The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s1413-86702003000600012
|View full text |Cite
|
Sign up to set email alerts
|

Septic arthritis as the first sign of Candida tropicalis fungaemia in an acute lymphoid leukemia patient

Abstract: Fungal infections caused by Candida species have increased in incidence during the past two decades in England, North America and Europe. Candidal arthritis is rare in patients who are not intravenous drug users or are who not using a prostheses. We report the case of a 24-year-old man with acute lymphoid leukemia, who developed Candida tropicalis arthritis during an aplastic period after chemotherapy. This is the eighth case described in the literature of C. tropicalis causing arthritis without intra-articula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…In our study, one adult with septic arthritis of the hip had decreased perfusion of the femoral epiphysis on MRI, and Candida tropicalis grew on culture of aspirate. C. tropicalis arthritis has been found in patients with hematologic malignant disease, and septic arthritis can be the first sign of C. tropicalis infection [31][32][33][34]. Our patient later proved to have hemophagocytic lymphohistiocytosis.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, one adult with septic arthritis of the hip had decreased perfusion of the femoral epiphysis on MRI, and Candida tropicalis grew on culture of aspirate. C. tropicalis arthritis has been found in patients with hematologic malignant disease, and septic arthritis can be the first sign of C. tropicalis infection [31][32][33][34]. Our patient later proved to have hemophagocytic lymphohistiocytosis.…”
Section: Discussionmentioning
confidence: 68%
“…Articular structures can be affected by mycotic infections through direct inoculation, contiguous spread, or hematogenous dissemination [ 1 - 4 ]. Of the various Candida species, Candida albicans is most commonly associated with fungal arthritis, especially in immunocompromized individuals [ 4 - 7 ]. Typically infection predominates in large weight-bearing joints, most often the knee [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its toxicity, AmB was the initial drug used in 68% cases of Candida arthritis [5,8,13] and its good penetration into the synovial fluid has been shown when given intravenously [15]. Farrell et al [15] concluded that adequate synovial fluid concentration of AmB was achieved during systemic therapy and intra-articular administration was ordinarily unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal arthritis is a relatively rare complication that occurs in neutropenic patients with hematological disease and cancer especially those receiving prophylactic FCZ and broad-spectrum antibiotics. C. albicans has been reported to be the most common species causing fungal arthritis [3] followed by Candida tropicalis (C. tropicalis) [4][5][6][7][8][9], while C. krusei still remains very rare [9][10][11].…”
Section: Introduction mentioning
confidence: 99%